Sosialisasi PHBS dengan Media Komunikasi pada Siswa Madrasah Ibtidaiyah Mathla’ul Anwar Cilajim Desa Cipendeuy Kabupaten Lebak, Banten - Sofia Wardhani; Vina Mahdalena; Lusia Handayani (Jurnal Pengabdian Pada Masyarakat, 2020)
PHBS SOCIALIZATION USING COMMUNICATION MEDIA AMONG STUDENTS OF MADRASAH IBTIDAIYAH MATHLA'UL ANWAR OF CILAJIM, CIPENDEUY VILLAGE, LEBAK. One of Indonesian Government effort to increase community health status is through PHBS (Perilaku Hidup Bersih dan Sehat) campaign. RISKESDAS 2013 data showed only 34,2% of Household in Banten practicing PHBS. There are five campaign group target, one of them are school community. We choose student of madrasah ibtidaiyah Matla’ul Andwar Cilajim desa Cipendeuy as responden because from previous observation there were a lot of student that didn’t practice PHBS, in this case washing hands with soap. Method. Audio visual using video and sing with song that created by the team and practicing washing hands with soap. Conclucion. All of the first year students (30) practicing the song and washing hands with soap and end with test.